Study on pathogenicity of Colletotrichum gloeosporioides on Coffee in North of Vietnam - Ha, Nguyen Thanh; Ngat, Hoang Thi; Thu Ha, Nguyen Thi; Hoi, Pham Xuan (Academia Journal of Biology, 2012)
Coffee is an important crop in Vietnam and it has recently brought a lot of benefit for the country through export. After coffee leaf rust, anthracnose is the second destructive disease for coffee production and is caused primarily by Colletotrichum gloeosporioides. In order to investigate the pathogenicity of C. gloeosporioides on coffee in the North of Vietnam, we carried out isolation of C. gloeosporioides species from different coffee plantations and found that C. gloeosporioides presents in different parts of coffee including leaf, twig, ripe berry and green berry. The pathogenicity of a total of twenty eight C. gloeosporioides isolates was tested on green berry in laboratory. Interestingly, two most pathogenic isolates were originated from green berry. In detail, the rate of green berry infection by C. gloeosporioides isolates varied from 4.44% to 76.67% and the variation of infection rate was also observed clearly among C. gloeosporioides isolates originating from leaf (14.40% to 45.56%), twig (4.44% to 58.89%), ripe berry (22.20% to 61.10%) and green berry (24.40% to 76.67%). Three selected pathogenic isolates representing for C. gloeosporioides isolates originated from twig, ripe berry and green berry were further tested for pathogenicity on hypocotyl seedling in greenhouse. The rate of hypocotyl seedling infection by C. gloeosporioides isolates originated from twig, green berry and ripe berry is 48.89%, 37.78 and 23.33% respectively. Our data suggests that pathogenicity of C. gloeosporioides is variable and specific among isolates, parts of coffee.